Risk Culture in Financial Institutions - Ramsay-Lewis, Jordan/JRL (2015)
Over the last two decades, the financial services industry has constantly been in the spotlight because of large-scale financial losses and complete failure. Some organisations include Barings Bank, UBS, Société Génerale and AIG, who all suffered massive losses due to incompetence and fraud. While previous research has focussed on market, credit and operational risk, there is still a lack of research for preventing operational risk. However, the correct ‘risk culture’ - a fairly new term – is crucial for managing and preventing operational risk. This has led to the term being one of the most prominent topics in the financial services industry today. This paper explores the top 15 final notices from each year, issued by the FCA for over £1,000,000 from 2012 – 2014 in order to find a common theme in the risk culture of financial institutions. In order to categorise the final notices, a framework by the Institute of Risk Management (2012) has been adopted. This framework will be applied to the NVivo software which will allow the final notices to be accurately analysed.